Daily Performance Profile Comparison Test of Monocrystalline and Poly-Crystalline Solar Panels - Primasari Cahya Wardhani; Nur Aini Fauziyah; Aulia Dewi Fatikasari; Bagas Aryaseta; Achmad Dzulfiqar Alfiansyah (Nusantara Science and Technology Proceedings, 2022)
The use of electrical energy for each region is increasing every year, along with the community’s increasing needs. Surabaya, a metropolis in Indonesia, is listed as the third-largest user of electrical energy in Indonesia. The community has widely used solar panels as new renewable energy, such as in the construction of traffic lights, street lighting, and several households. This study aims to determine the daily performance profile of the daily value of voltage, current, and energy stored from solar panels with different types of solar panels, namely, using polycrystalline and monocrystalline solar panels mounted on the roof of the house. Data retrieval was carried out with an interval of data collection every hour when the sun is high enough until the afternoon (06:00 WIB – 18:00 WIB). The results showed that the average voltage value for monocrystalline solar panels was 21.09 V and polycrystalline solar panels were 19.32 V. In addition, the output current values for monocrystalline and polycrystalline solar panels were 0.903 A and 0.27 A. Meanwhile, the monocrystalline output power value was 19.72 W and polycrystalline 5.43 W. Based on the research data, it can be concluded that the energy stored in the battery and the efficiency value for each monocrystalline solar panel produces a higher output value than that produced by polycrystalline solar panels, 12,98%, and 4.04%. However, polycrystalline solar panels that produce a lower and stable electric current can extend the lifetime of the battery where the electric charge is stored from the solar panel.